Pelatihan Pengolahan Es Krim Yogurt sebagai Upaya Peningkatan Daya Saing dan Diversifikasi Produk di UMKM Yogurt Sehati - Faizah, Faizah; Dyah Kurniawati, Ajeng; Latifasari, Nurul; Setiya Rafika Nur, Yohani (JURPIKAT, 2026)
Yogurt Sehati, a local yogurt producer in Purwokerto, faces challenges in sustaining its business due to stagnant income and limited product variety. This community service program aimed to enhance competitiveness and encourage product diversification through a training program on yogurt ice cream processing, a value-added product derived from fermented milk. The activity was conducted using a Participatory Action Research (PAR) approach, including surveys, focus group discussions (FGDs), interviews, socialization, technical training, and evaluation. The partner in this program was UMKM Yogurt Sehati located in Purwonegoro Village, North Purwokerto District, Banyumas Regency, involving 15 participants including the owner, employees, and resellers. The training outcomes showed that 85% of participants found the materials easy to understand, and 90% successfully practiced yogurt ice cream production. Additionally, post-test results indicated increased understanding of the importance of product innovation for business sustainability. This program successfully improved the partner's skills, introduced a high-value alternative product, and opened opportunities to increase income through product diversification.